Characterization of Highly Mucus-Adherent Non-GMO Derivatives of Lacticaseibacillus rhamnosus GG - Rasinkangas, Pia; Tytgat, Hanne L. P.; Ritari, Jarmo; Reunanen, Justus; Salminen, Seppo; Palva, Airi; Douillard, François P.; de Vos, Willem M. (Frontiers in Bioengineering and Biotechnology, 2020)
Lacticaseibacillus rhamnosus GG is one of the best studied lactic acid bacteria in the context of probiotic effects. L. rhamnosus GG has been shown to prevent diarrhea in children and adults and has been implicated to have mitigating or preventive effects in several disorders connected to microbiota dysbiosis. The probiotic effects are largely attributed to its adhesive heterotrimeric sortase-dependent pili, encoded by the spaCBA-srtC1 gene cluster. Indeed, the strain-specific SpaCBA pili have been shown to contribute to adherence, biofilm formation and host signaling. In this work we set out to generate non-GMO derivatives of L. rhamnosus GG that adhere stronger to mucus compared to the wild-type strain using chemical mutagenesis. We selected 13 derivatives that showed an increased mucus-adherent phenotype. Deep shotgun resequencing of the strains enabled division of the strains into three classes, two of which revealed SNPs (single nucleotide polymorphisms) in the spaA and spaC genes encoding the shaft and tip adhesive pilins, respectively. Strikingly, the other class derivatives demonstrated less clear genotype – phenotype relationships, illustrating that pili biogenesis and structure is also affected by other processes. Further characterization of the different classes of derivatives was performed by PacBio SMRT sequencing and RNAseq analysis, which resulted in the identification of molecular candidates driving pilin biosynthesis and functionality. In conclusion, we report on the generation and characterization of three classes of strongly adherent L. rhamnosus GG derivatives that show an increase in adhesion to mucus. These are of special interest as they provide a window on processes and genes driving piliation and its control in L. rhamnosus GG and offer a variety of non-GMO derivatives of this key probiotic strain that are applicable in food products.